The Correlation between Allergic Diseases and Systemic Lupus Erythematosus - Pratiwi, Dewi; Wediningsih, Yulyani; Matea, Ari; Nareswari, Kirana Pawitra; Aryani, Niken Dyah (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: The prevalence of autoimmune diseases and major chronic allergic diseases such as allergic rhinitis, asthma, and atopic dermatitis are increasing in line with the occurrence of climate change. Allergy and systemic lupus erythematosus (SLE) are sometimes being linked since both are immune diseases involving gene-environment interactions. The purpose of this research is to investigate the correlation between allergic diseases and SLE.Method: This case-control study was performed on 39 SLE subjects from the Tittari Community and 39 non-SLE subjects aged 15-49 years old, from September until October 2021. All of them were females. The independent variable was allergic disease and the dependent variable was SLE. Participants' characteristics and allergy data were collected through answering the online Score for Allergic Rhinitis (SFAR) questionnaire, then the results were processed with bivariate and multivariate analyses.Results: The correlation between allergic diseases and SLE was significant for atopic dermatitis but not for allergic rhinitis and asthma (p=0.018; p=0.352; p=0.151 respectively). The bivariate analysis revealed that the risk of SLE was 3.17 times higher in atopic dermatitis patients (OR=3.17; 95% CI=1.20-8.39; p=0.018). Furthermore, the multivariate analysis found that subjects with atopic dermatitis had the highest risk of SLE (OR= 3.18; 95% CI= 1.07-9.51; p=0.031).Conclusion: Among allergic diseases, atopic dermatitis was found to be significantly correlated with SLE, where the risk of SLE was raised as the number of atopic dermatitis increased.Keywords: systemic lupus erythematosus, allergic diseases, allergic rhinitis, asthma, atopic dermatitisCorrespondence: Dewi Pratiwi. Department of Otorhinolaryngology Head and Neck Surgery, Faculty of Medicine, Universitas Sebelas Maret – Moewardi Hospital, Indonesia. Email: pratiwidewi81@staff.uns.ac.id. Phone: (0271) 664569.Indonesian Journal of Medicine (2022), 07(01): 19-27https://doi.org/10.26911/theijmed.2022.07.01.03